Design and experimental verification of smart aileron structure based on Shape Memory Alloy. Issue 3 (May 2019) - Liu, S W; Li, F
Abstract: In traditional smart aileron structures, a pair of Shape Memory Alloy (SMA) wire is arranged on one side of the rib. Although large deformation angle could be achieved, the overall driving speed is relatively slow because of the long cooling time of SMA. To improve the speed, we designed the structure with multiple SMA wires being arranged on both sides of the rib. Theoretical analysis showed that this structure could improve the driving speed by reducing the cooling time during each deformation cycle. After measuring the parameters of SMA, we processed ANSYS simulation to analyze the deformation angle. Results showed that in the new structure, the upward angle was 92% of the existing structure and the downward angle was 67% of the existing structure. These losses were acceptable as the deformation angle has already been large enough. Finally, experiments were processed to determine the required driving time as well as verify the simulation results. In the new structure, the speed was increased by about 44%. Besides, the upward and downward deformation angles of the new structure were 90% and 65% of the existing one, which were close to the simulation results.